2017
DOI: 10.31234/osf.io/gy4j2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unearthing the “green” personality: Core traits predict environmentally friendly behavior

Abstract: Pro-environmental attitudes and behaviors show substantial individual differences, and exploringtheir predictors can help reveal the origins of pro-environmental behavior. Basic personality traits may provide a partial explanation, but it is unclear which personality traits are reliably associated with pro-environmental behaviors. The current paper uses a specific type of environmental behavior, reducing greenhouse gas emissions, to clarify which personality correlates are most robustly associated with behavio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
109
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(130 citation statements)
references
References 26 publications
17
109
4
Order By: Relevance
“…As a side note, our analyses revealed some exploratory findings regarding broader personality correlates of pro‐environmental behaviour. Along the lines of previous research (Brick & Lewis, ; Busic‐Sontic et al, ; Hilbig et al, ; Lee et al, ; Markowitz et al, ; Ojedokun, ; Terrier et al, ), openness to experience was found to be the Big Five trait most closely linked to self‐reported pro‐environmental behaviour in our study. Our data further suggest, for the first time, that this relationship also extends to an objective measure of actual pro‐environmental behaviour (i.e.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As a side note, our analyses revealed some exploratory findings regarding broader personality correlates of pro‐environmental behaviour. Along the lines of previous research (Brick & Lewis, ; Busic‐Sontic et al, ; Hilbig et al, ; Lee et al, ; Markowitz et al, ; Ojedokun, ; Terrier et al, ), openness to experience was found to be the Big Five trait most closely linked to self‐reported pro‐environmental behaviour in our study. Our data further suggest, for the first time, that this relationship also extends to an objective measure of actual pro‐environmental behaviour (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…Along the lines of cognitive flexibility, pro‐environmental behaviour has been found to relate to individual differences in openness to experience in multiple studies (Brick & Lewis, ; Busic‐Sontic, Czap, & Fuerst, ; Hilbig, Zettler, Moshagen, & Heydasch, ; Lee, Ashton, Choi, & Zachariassen, ; Markowitz, Goldberg, Ashton, & Lee, ; Ojedokun, ; Terrier, Kim, & Fernandez, ). With correlations ranging between r = .23 and r = .43, openness appears to be the Big Five factor most closely related to pro‐environmental behaviour.…”
Section: Cognitive Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The findings also acknowledged another limitation of a perception survey instrument -complexity of data interpretations. There are complex factors, such as students' personality types (Brick and Lewis, 2016); situational factors (Corraliza and Berenguer, 2000); and emotional and attitude factors (Pooley and O'Connor, 2000), that might affect students' perceptions of their sustainability-related behavior change. The findings also supported our initial assumption that students might learn sustainability as part of their exam preparation, disconnected from real life experiences.…”
Section: Students' Perceptions Of the Effect Of Liberal Studies Progrmentioning
confidence: 99%
“…Markowitz et al (2012) showed a positive impact of Openness to Experience on environmental habits, such as using public transportation, carpooling and composting food scraps. Similarly, Brick & Lewis (2016) demonstrated that Openness to Experience, Conscientiousness and Extraversion are positively related to environmental attitudes, which in turn have an impact on pro-environmental activities (e.g. recycling, conserving water, using public transportation).…”
mentioning
confidence: 99%